IMPLEMENTASI AJARAN TRI HITA KARANA DALAM PENGEMBANGAN ASPEK SOSIAL ANAK USIA DINI DI TAMAN KANAK-KANAK KEMALA BHAYANGKARI KABUPATEN PATI - Setyaningsih; Sugiman (Lembaga Penerbit Sekolah Tinggi Hindu Dharma Klaten, 2020)
Through religious education, Hindu students are guided to always foster harmonious relations between human beings, the natural surroundings or the environment as well as relationships with God. These three relationships are in accordance with the concept of Tri Hita Karana, to shape the character of children from an early age. Early childhood growth will affect the next period i.e. the attainment of maturity in social relations. This research would like to overview the early childhood development precisely and maximally, so the result will be able to develop all aspects of the scope of child development including social aspects. The goal in this research is to describe the early childhood social development in kindergarten (TK) Kemala Bhayangkari No. 43 Kabupaten Pati by using qualitative approach. The results showed that (1) the early childhood social abilities in kindergarten Kemala Bhayangkari No. 43 Kabupaten Pati include the ability to get along, socialize and properly communicate with friends and teachers, working together, being patient in taking turn, caring and helping friends who is in trouble in classroom tasks, sharing food and toys, giving up to friends and being responsible.